CLOUD TECHNOLOGY DISTANCE LEARNING IN HIGHER MATHEMATICS LEARNING PROCESS - Rashevska, Н.В. (Journal of Information Technologies in Education (ITE), 2014)
The article singles out four types of learning models: the model of distance education without the use of global networks, network model of e-learning, mobile learning model and the model of cloud technologies for distance learning can help you organize the teaching of Mathematics. Mentioned advantages and disadvantages of cloud technologies for distance learning.